1983
DOI: 10.1159/000123514
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Foot-Shock Induced Analgesia: Glucocorticoids and Non-Pituitary Opioids Are Involved

Abstract: In rats, the analgesic response induced by prolonged intermittent foot-shock is abolished by naloxone or adrenalectomy, and is restored in adrenalectomized animals by the administration of dexamethasone or corticosterone, but not deoxycorticosterone. Levels of immunoreactive β-endorphin in the anterior pituitary are significantly elevated by adrenalectomy alone, and further by dexamethasone and corticosterone; in contrast, immunoreactive β-endorphin levels in the neuro-intermediate lobe are raised by deoxycort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…It is generally agreed that the anterior pituitary is the main source of peripheral {3-EP I -31 (Guillemin et al 1977;Smyth and Zakarian 1980), but to what degree peripheral {3-EP I -31 modulates pain perception (Melzack and Wall 1965), or under what conditions the anterior pituitary contributes to concentrations in the brain (Bergland and Page 1979), or cerebrospinal fluid after electro-acupuncture (Sjolund et al 1977;Clement-Jones et al 1980), is still controversial (Rossier et al 1977;Lim et al 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally agreed that the anterior pituitary is the main source of peripheral {3-EP I -31 (Guillemin et al 1977;Smyth and Zakarian 1980), but to what degree peripheral {3-EP I -31 modulates pain perception (Melzack and Wall 1965), or under what conditions the anterior pituitary contributes to concentrations in the brain (Bergland and Page 1979), or cerebrospinal fluid after electro-acupuncture (Sjolund et al 1977;Clement-Jones et al 1980), is still controversial (Rossier et al 1977;Lim et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…With the much studied footshock-induced analgesia, a role for glucocorticoids in mediating this phenomenon has been found (MacLennan et al 1982;Lim et al 1983), in that analgesia is restored in adrenalectomized rats by corticosterone or dexamethasone. In the present studies there was a marked increase in the physiologically active plasma 'free' cortisol that was highly correlated with total assayable cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…That stress hormones have such an effect is indicated by the occurrence of stress-induced analgesia, in which stress both blunts affective reactions to pain and raises pain thresholds (Horvath & Kekesi, 2006; Sapolsky, 1992)—effects which have been shown to involve activation of somatosensory cortices, as well as AIC and ACC (Yilmaz et al, 2010). 25 Glucocorticoids (e.g., cortisol, corticosterone) are known to have both analgesic effects (e.g., Hargreaves, Mueller, Dubner, Goldstein, & Dionne, 1987; Lim, Oei, & Funder, 1983) and a variety of other effects on motivated behaviors such as eating and drinking (e.g., Erickson, Drevets, & Schulkin, 2003; la Fleur, 2006)—with both low and high levels associated with reduced hunger (e.g., Dallman et al, 1993; Leibowitz, 1995).…”
Section: Evidence Implicating Somatic Signals and Interoceptive Dysfu...mentioning
confidence: 99%
“…The effect of ADX is a long-lasting phenomenon persisting for a period as long as 7 or even 14 days. A similar long-term effect was obser ved also for stress-induced analgesia (15,20,21]. MacLennan et al [21] suggested that corticosterone is of critical im portance in the development of the long-term opioid form of stress-induced analgesia.…”
Section: Discussionmentioning
confidence: 66%